Spatial-Based Livestock Development Strategy in Berau Regency: An Integration of Location Quotient (LQ) and GIS Analysis - Aprylasari, Dede; Toyibulah, Yoga (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to map the potential of the livestock sector in Berau Regency using the Location Quotient (LQ) and Geographic Information System (GIS) approaches to identify basic commodities and their spatial distribution patterns. A quantitative approach was used to analyze secondary data from the Animal Husbandry Service and related agencies. At the same time, spatial analysis was conducted to visualize the distribution of livestock populations and regional development zoning. The results of the LQ analysis indicate that goats, buffalo, and cattle are basic commodities with significant contributions to the regional economy. Meanwhile, native chickens and ducks serve as complementary sources of food, supporting local food security. The results of the spatial mapping show a contrasting distribution pattern between inland and coastal areas. The integration of LQ and GIS resulted in a livestock development zoning consisting of: (1) a ruminant base zone in the central-southern region, (2) a poultry base zone in coastal and island areas, and (3) a support zone in non-base areas such as Tabalar and Teluk Bayur. These findings confirm that the development of the livestock subsector in Berau Regency requires a spatial and evidence-based planning approach to encourage land efficiency, economic equity, and environmental sustainability. Therefore, the results of this study can serve as a basis for strategic planning in the development of competitive and sustainable livestock areas at the regional level.